Synergistic reinforcement with SEBS-g-MAH for enhanced thermal stability and processability in GO/RGO-filled PC/ABS composites - Fatin Najwa, Joynal Abedin; Ahmad Noor Syimir, Fizal; Alkarkhi, Abbas F. M.; Nor Afifah, Khalil; Ahmad Naim, Ahmad Yahaya; Hossain, Md Sohrab; Sairul Izwan, Safie; Nurul Ain, Ismail; Muzafar, Zulkifli (MDPI, 2024)
The integration of compatibilisers with thermoplastics has revolutionised the field of polymer composites, enhancing their mechanical, thermal, and rheological properties. This study investigates the synergistic effects of incorporating SEBS-g-MAH on the mechanical, thermal, and rheological properties of polycarbonate/acrylonitrile-butadiene-styrene/graphene oxide (PC/ABS/GO) (PAGO) and the properties of polycarbonate/acrylonitrile-butadiene-styrene/graphene oxide (PC/ABS/rGO) (PArGO) composites through the melt blending method. The synergistic effects on thermal stability and processability were analysed by using thermogravimetry (TGA), melt flow index (MFI), and Fourier-transform infrared spectroscopy (FTIR). The addition of SEBS-g-MAH improved the elongation at break (EB) of PAGO and PArGO up to 33% and 73%, respectively, compared to the uncompatibilised composites. The impact strength of PAGO was synergistically enhanced by 75% with the incorporation of 5 phr SEBS-g-MAH. A thermal analysis revealed that SEBS-g-MAH improved the thermal stability of the composites, with an increase in the degradation temperature (T80%) of up to 17% for PAGO at 1 phr SEBS-g-MAH loading. The compatibilising effect of SEBS-g-MAH was confirmed by FTIR analysis, which indicated interactions between the maleic anhydride groups and the PC/ABS matrix and GO/rGO fillers. The rheological measurements showed that the incorporation of SEBS-g-MAH enhanced the melt flowability (MFI) of the composites, with a maximum increase of 38% observed for PC/ABS. These results demonstrate the potential of SEBS-g-MAH as a compatibiliser for improving the unnotched impact strength (mechanical), thermal, and rheological properties of PC/ABS/GO and PC/ABS/rGO composites, achieving a synergistic effect.